2010
DOI: 10.1128/jb.00278-10
|View full text |Cite
|
Sign up to set email alerts
|

RNA Processing of Nitrogenase Transcripts in the CyanobacteriumAnabaena variabilis

Abstract: Little is known about the regulation of nitrogenase genes in cyanobacteria. Transcription of the nifH1 and vnfH genes, encoding dinitrogenase reductases for the heterocyst-specific Mo-nitrogenase and the alternative V-nitrogenase, respectively, was studied by using a lacZ reporter. Despite evidence for a transcription start site just upstream of nifH1 and vnfH, promoter fragments that included these start sites did not drive the transcription of lacZ and, for nifH1, did not drive the expression of nifHDK1. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 63 publications
6
70
2
Order By: Relevance
“…A 6-kb SacI fragment of pRL2948a was arrow. The solid rightward arrows indicate transcription start sites (tss) upstream of nifB1, in nifU1, in nifE1, and upstream of hesA1, while the dashed arrows indicate transcription processing sites upstream of nifH1, in ava3935, and upstream of fdxH, as determined previously (33) and in this study. (B) ␤-Galactosidase activities for strains containing fusions of four different regions upstream of nifE1 to a promoterless lacZ.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…A 6-kb SacI fragment of pRL2948a was arrow. The solid rightward arrows indicate transcription start sites (tss) upstream of nifB1, in nifU1, in nifE1, and upstream of hesA1, while the dashed arrows indicate transcription processing sites upstream of nifH1, in ava3935, and upstream of fdxH, as determined previously (33) and in this study. (B) ␤-Galactosidase activities for strains containing fusions of four different regions upstream of nifE1 to a promoterless lacZ.…”
Section: Methodssupporting
confidence: 55%
“…Apparent transcription start sites have been identified upstream of nifB (25,26,(33)(34)(35), nifH (26,36), hesA (30,35), and fdxH (31). Although the putative nifH transcription start site has been identified several times, we were unable to drive transcription of lacZ using a DNA fragment that included the entire niU1-nifH1 intergenic region of A. variabilis, and we showed that the 5= end of the nifH1 transcript in A. variabilis is a processed transcript rather than a transcription initiation site; thus, there is no promoter upstream of nifH1 (33). In contrast, nifB1 has a promoter that initiates transcription, and there is a promoter within the coding region of nifU1 (33), which has been verified by transcriptome sequencing (RNA-seq) (35).…”
mentioning
confidence: 99%
“…Demonstrating direct regulation of nifH expression by SigE will require in vitro transcription assays using purified components. However, these experiments are especially challenging because the cis-acting sequences that constitute the nifH promoter have not been identified in Anabaena PCC 7120, and recent data with Anabaena variabilis suggest that multiple distant promoters and RNA-processing events may be involved in expression of the nifHDK operon (50).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the Anabaena PCC 7120 nifHDK operon has been studied for over 25 years (14,18,20,43,44,50,53); however, little is known about the transcription components that regulate this operon. Our results suggest that sigE is in -FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Ungerer et al (36) reported that the high expression of nifH1 is supported by two promoters: a strong one is located upstream of nifB1, and the other weak one is located in the coding region of nifU1 in A. variabilis. In addition, they pointed out that a secondary structure of 5′ UTR just upstream of nifH1 might contribute to stabilize the processed nifH1 transcript.…”
Section: Discussionmentioning
confidence: 99%